Disruption of hemochromatosis protein and transferrin receptor 2 causes iron-induced liver injury in mice. - Delima, R.; Chua, A.; Tirnitz-Parker, Janina; Gan, E.; Croft, K.; Graham, Ross; Olynyk, John; Trinder, D. (John Wiley & Sons Inc., 2012)
Mutations in hemochromatosis protein (HFE) or transferrin receptor 2 (TFR2) cause hereditary hemochromatosis (HH) by impeding production of the liver iron-regulatory hormone, hepcidin (HAMP). This study examined the effects of disruption of Hfe or Tfr2, either alone or together, on liver iron loading and injury in mouse models of HH. Iron status was determined in Hfe knockout (Hfe−/−), Tfr2 Y245X mutant (Tfr2mut), and double-mutant (Hfe−/−×Tfr2mut) mice by measuring plasma and liver iron levels. Plasma alanine transaminase (ALT) activity, liver histology, and collagen deposition were evaluated to assess liver injury. Hepatic oxidative stress was assessed by measuring superoxide dismutase (SOD) activity and F2-isoprostane levels. Gene expression was measured by real-time polymerase chain reaction. Hfe−/−×Tfr2mut mice had elevated hepatic iron with a periportal distribution and increased plasma iron, transferrin saturation, and non-transferrin-bound iron, compared with Hfe−/−, Tfr2mut, and wild-type (WT) mice. Hamp1 expression was reduced to 40% (Hfe−/− and Tfr2mut) and 1% (Hfe−/−×Tfr2mut) of WT values. Hfe−/− ×Tfr2mut mice had elevated plasma ALT activity and mild hepatic inflammation with scattered aggregates of infiltrating inflammatory cluster of differentiation 45 (CD45)–positive cells. Increased hepatic hydoxyproline levels as well as Sirius red and Masson's Trichrome staining demonstrated advanced portal collagen deposition. Hfe−/− and Tfr2mut mice had less hepatic inflammation and collagen deposition. Liver F2-isoprostane levels were elevated, and copper/zinc and manganese SOD activities decreased in Hfe−/−×Tfr2mut, Tfr2mut, and Hfe−/− mice, compared with WT mice.Conclusion: Disruption of both Hfe and Tfr2 caused more severe hepatic iron overload with more advanced lipid peroxidation, inflammation, and portal fibrosis than was observed with the disruption of either gene alone. The Hfe−/−×Tfr2mut mouse model of iron-induced liver injury reflects the liver injury phenotype observed in human HH.